N6-methyladenosine-modified lncRNA and mRNA modification profiles in cerebral ischemia-reperfusion injury - Shao, Le; Chen, Bowei; Wu, Qibiao; Xu, Yaqian; Yi, Jian; Guo, Zhihua; Liu, Baiyan (Frontiers in Genetics, 2022)
Cerebral ischemia-reperfusion injury (CIRI) is common in ischemic stroke and seriously affects the prognosis of patients. At present, N6-methyladenosine (m6A) modification of lncRNAs and mRNAs has been reported in other diseases, such as cancer, but its role in CIRI has not been clarified. In this study, we aimed to investigate the m6A lncRNA and m6A mRNA modification profiles in CIRI. First, we detected the total level of m6A and the changes in related m6A methyltransferases and demethylases in the brain tissue of rats with CIRI and then identified differentially modified lncRNAs and mRNAs in CIRI by lncRNA and mRNA epigenetic transcriptomic microarray. In addition, bioinformatics analysis was used to predict the underlying functions and related pathways of related lncRNAs and mRNAs. We found that the total m6A methylation level was significantly increased, and the expression of fat mass and obesity-associated protein (FTO) was downregulated after CIRI. In addition, a large number of m6A-modified lncRNAs and mRNAs appeared after CIRI, and these genes were mainly enriched for the Toll-like receptor signaling pathway, peroxisome proliferator-activated receptor (PPAR) signaling pathway, and mitogen-activated protein kinase (MAPK) signaling pathway. Our findings provide the basis and insights for further studies on m6A modification in CIRI.